DIVERSITY OF XYLOSE ASSIMILATING YEAST FROM THE ISLAND OF ENGGANO, SUMATERA, INDONESIA [Keragaman Khamir Pengguna Xilose yang Diisolasi dari Pulau Enggano, Sumatera, Indonesia] - Atit Kanti; I Nyoman Sumerta (BERITA BIOLOGI, 2016)
Naturally occurring yeasts (wild type) are important genetic resources for many industrial interests. Though biodiversity exploration of Enggano has been done since 1944, but there is no report for yeast diversity from this island. Due to its industrial interest, xylose fermenting yeast is target for many scientists. This present study aims to isolate xylose assimilating yeast from island of Enggano. The samples were collected from varying sources included soil, leaf litter, decay wood, fruit and sediment. Xylose enrichment culture technique was performed to enrich xylose fermenting yeast. While for the isolation of yeast several methods which include dilution, ballistopore falling, direct isolation, membrane filtration were done. Of 200 isolates, 76 strains (38 %) were xylose assimilating yeast which mostly belong to Candida which include C. insectorum, C. tropicalis, C. boidinii, C. pseudolambica, C. yuanshanica, C. silvae, Cyberlindnera saturnus, Williopsis saturnus and Sporobolomyces poonsookiae. One strain Candida sp. that was isolated from soil could be assigned as a candidate of novel species on base on its morphological and biochemical characteristics along with analyses of gene sequence from D1/D2 domain. This study confirms that yeast survey is very important to obtain new genetic resources for industrial interest as well as for taxonomic study.